TINGKAT KEMENARIKAN NILAI-NILAI KEARIFAN LOKAL DESA BUGISAN BERDASARKAN PERSEPSI WISATAWAN DAN MASYARAKAT LOKAL - Annisaa Nurul Atiqah; Rekta Deskarina (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
Plaosan Temple is one of the famous new tourist destinations at the moment located in Bugisan Village, Prambanan District, Klaten Regency, Central Java. Beautiful natural conditions become part of the attraction of a tour in the village of Bugisan. In addition to the natural conditions, the Bugisan Village has several values of local wisdom that have been passed down from generation to generation by the local community. This study aims to assess the perceptions of tourists and local communities regarding the values of local wisdom in the Bugisan Village. Based on the value of local wisdom in the Bugisan Village include (1) Cultural Arts: Srandul, Jathilan, Campur Sari, Gejog Lesung, Karawitan, (2)Myth: Mbah Budho Mound and Njama Keris, (3) Socio- Economy: Agriculture, Trade, Crafts, Traditional Transportation Models, (4)Local Architecture. Based on the perceptions of tourists and local people, art and culture aspects are considered the most interesting and potential to be developed as the main attraction in the Bugisan Village.Keywords: attractiveness level, bugisan village, local wisdom